Insights into maternal and neonatal anti-Ro/SSA antibodies: implications on pregnancy and neonatal health - Al Emadi, Samar; Satti, Eman; Hadwan, Nawal (Frontiers in Lupus, 2024)
Research on obstetric and fetal complications in patients with anti-Ro/SSA positivity is of significant interest. However, the evidence regarding this subject is scarce. Therefore, in this study, we evaluated the effect of the association between anti-Ro/SSA antibodies and adverse maternal and neonatal outcomes. We included 79 pregnant women (132 pregnancies) with confirmed anti-Ro/SSA positivity. The results showed that, of the total pregnancies, 20% resulted in miscarriage, 5% resulted in intrauterine fetal demise (IUFD), and 17% of the 99 live births were preterm. Moreover, 12% of the babies had low birth weights, and this percentage was higher among those with SLE. In this cohort, two neonates had congenital heart block (2%) and 1 had neonatal lupus (1%). We observed that women who received hydroxychloroquine had lower rates of miscarriage and IUFD. Further, we believe that this paper will be of interest to the readership of your journal because this is the first study to shed light on autoimmune diseases in pregnant women in this geographical region and to provide a description of neonatal anti-Ro titers. It is also a rare report documenting anti-Ro/SSA titers in neonates. These findings can serve as a foundation for future in-depth research on this topic.